Errantum: Treatment of human astrocytoma U87 cells with silicon dioxide nanoparticles lowers their survival and alters their expression of mitochondrial and cell signaling proteins - Lai JCK (Dove Medical Press, 2010)
Lai JCK, Ananthakrishnan G, Jandhyam S, et al. Treatment of human astrocytoma U87 cells with silicon dioxide nanoparticles lowers their survival and alters their expression of mitochondrial and cell signaling proteins. Int J Nanomedicine. 2010;5:715–723.The wrong image was used in Figure 5 on page 719.